Differential expression of novel biomarkers (TLR‐2, TLR‐4, COX‐2, and Nrf‐2) of inflammation and oxidative stress in semen of leukocytospermia patients. (30th July 2015) - Hagan, S.; Khurana, N.; Chandra, S.; Abdel‐Mageed, A. B.; Mondal, D.; Hellstrom, W. J. G.; Sikka, S. C.
Summary Chronic genitourinary inflammation results in Leukocytospermia (LCS), an elevated number of white blood cells (WBCs) in semen, which, in association with oxidative stress, may suppress sperm function, and manifest as male factor infertility. The current clinical diagnosis of LCS employs manual enumeration of WBCs and requires complex staining and laboratory skills or measurement of inflammatory cytokines and chemokines levels. Many patients with idiopathic infertility are asymptomatic. In search of better inflammatory markers for LCS, we evaluated expression of toll‐like receptors 2 and 4 (TLR‐2/4), cyclooxygenase‐2 (COX‐2), and nuclear factor (erythroid‐derived 2)‐like 2 (Nrf‐2) in semen samples of age‐matched infertile patients with and without LCS. We employed the usage of specific Western blot evaluation, cytokine array; immunofluorescence microscopy (IFM) followed by computer‐based analysis, and other molecular approaches. As compared with non‐LCS patients (n = 38), semen samples from LCS patients (n = 47) displayed significantly lower total sperm count (p < 0.01), motility (p < 0.0001), normal head count (p < 0.0001), and a significantly higher white blood cell count (p < 0.0001). Differential cytokine profiling of seminal plasma by antibody array revealed up‐regulation of several pro‐inflammatory chemokines in LCS samples. Western blot analysis of LCS seminal plasma (n = 15) also showed a significant increase in expression of TLR‐2 (p < 0.001) and 4 (p < 0.01), COX‐2 (p < 0.001), and Nrf‐2 (p < 0.001) as compared with semen samples from non‐LCS patients (n = 15). Computer‐based objective IFM analysis of spermatozoa from LCS patients showed increased expression of TLR‐4 (p < 0.001), Cox‐2 (p < 0.01), and (Nrf‐2) (p < 0.01). Significant differences in the subcellular localization of these proteins were evident in the sperm head and tail segments of LCS samples. Altogether, these observations suggest that TLR‐2/4, COX‐2, and Nrf‐2 can serve as novel biomarkers of inflammation and oxidative stress. Therefore, developing a rapid assay for these biomarkers may facilitate early diagnosis and management of LCS especially in idiopathic and asymptomatic male infertility patients.